2003
DOI: 10.1126/science.1092053
|View full text |Cite
|
Sign up to set email alerts
|

Cell Migration: Integrating Signals from Front to Back

Abstract: Cell migration is a highly integrated multistep process that orchestrates embryonic morphogenesis; contributes to tissue repair and regeneration; and drives disease progression in cancer, mental retardation, atherosclerosis, and arthritis. The migrating cell is highly polarized with complex regulatory pathways that spatially and temporally integrate its component processes. This review describes the mechanisms underlying the major steps of migration and the signaling pathways that regulate them, and outlines r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

85
4,420
4
53

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 4,392 publications
(4,562 citation statements)
references
References 55 publications
85
4,420
4
53
Order By: Relevance
“…1) (Lauffenburger and Horwitz, 1996;Pollard and Borisy, 2003;Ridley et al, 2003). The major structures that define the leading edge activity of a migrating cell are lamella, lamellipodia, and filopodia.…”
Section: Basic Principles Of Cell Migration Overall Structure Of Thementioning
confidence: 99%
See 2 more Smart Citations
“…1) (Lauffenburger and Horwitz, 1996;Pollard and Borisy, 2003;Ridley et al, 2003). The major structures that define the leading edge activity of a migrating cell are lamella, lamellipodia, and filopodia.…”
Section: Basic Principles Of Cell Migration Overall Structure Of Thementioning
confidence: 99%
“…Polarization-In order to move in a certain direction, a cell first needs to polarize in that direction, i.e., to define its front (that will move forward) and its back (that will remain in the rear and retract as the leading edge protrudes). The central regulators of establishing this polarity are Rho family small GTPase Cdc42 (Etienne-Manneville and Hall, 2001;Itoh et al, 2002), Par proteins, and atypical protein kinase (aPKC) (see (Ridley et al, 2003) for overview). Additional signals are provided by a gradient of phosphatidylinositol triphosphate (PIP3) (decreasing from front to rear), produced by the action of phosphoinositide-3 kinase (PI3K), and regulated by PTEN, a PIP3 phosphatase, which is located to the cell rear and controls the lower level of PIP3 at the trailing edge.…”
Section: Basic Principles Of Cell Migration Overall Structure Of Thementioning
confidence: 99%
See 1 more Smart Citation
“…3 Cells interact with ECM components via heterodimeric cell surface proteins called integrins. 4 ECM-integrin interaction stimulates signal transduction pathways that regulate a number of cellular processes important in cancer growth, including cell cycle transition and protection from apoptosis. 4 We have shown that adhesion of SCLC cells via b1 integrins to ECM components promotes cell survival and confers resistance to chemotherapeutic agents.…”
Section: Introductionmentioning
confidence: 99%
“…4 ECM-integrin interaction stimulates signal transduction pathways that regulate a number of cellular processes important in cancer growth, including cell cycle transition and protection from apoptosis. 4 We have shown that adhesion of SCLC cells via b1 integrins to ECM components promotes cell survival and confers resistance to chemotherapeutic agents. 3 This has now been demonstrated to be a general mechanism for acquired drug resistance in a number of malignancies including myeloma, breast and colon cancer.…”
Section: Introductionmentioning
confidence: 99%